Amended definitions for Aplysinidae and Aplysina (Porifera, Demospongiae, Verongiida): on three new species from a remarkable population in the Gulf of California - Gómez, Patricia; González-Acosta, Bárbara; Sánchez-Ortíz, Carlos; Hoffman, Zvi; Hernández-Guerrero, Claudia J. (Zootaxa, 2018)
Verongiid sponges inhabiting the La Paz region, Gulf of California are described herein as new species. Although morphological evidence was sufficient to determine the identity between species, we have confirmed their uniqueness and relationships with molecular (CO1 and ITS1 and 2), and ecological studies. An amended definition of family Aplysinidae and genus Aplysina is presented to highlight a novel skeletal trait for the latter, clearly described herein as a complex of dendritic fibers sustained by anastomosed fibers deep in the choanosome. This novel fiber arrangement combination is a constant trait of Aplysina encarnacionae sp. nov. and A. airapii sp. nov., which otherwise conform to our current concept of Aplysina. The former species has a long tubular morphology, reddish purple color, with the longest dendritic fibers; while A. airapii sp. nov. is a short tubular sponge, yellow with reddish tints, and smaller choanosomal dendritic fibers that depart from a uniplanar anastomosed skeleton. A third species, A. sinuscaliforniensis sp. nov., is characterized by a completely anastomosed skeleton, massive habit with short tubes superimposed one over the other, sympatric with the other new species. Comparisons with Suberea azteca verified that the same novel skeletal architecture described here occurs in the latter, while Aiolochroia thiona examined as well, proved to bear an anastomosed skeleton only, besides sharing more features with Aplysina than with any other genera in Verongiida. Moreover, molecular sequencing recovered “S.” azteca nested in the Aplysina clade, prompting us to reallocate it in Aplysina, as originally proposed. The new species described herein are probably endemics within the Gulf of California since they have not been recorded elsewhere along the Mexican Pacific coast.